2017
DOI: 10.1097/md.0000000000007813
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of 18F-FDG-PET/CT parameters in patients with pancreatic carcinoma

Abstract: Background:The identification of pancreatic carcinoma (PC) patients with poor prognosis is a priority in clinical oncology because of their high 5-year mortality. However, the prognostic value of pretreatment 18F-fluorodeoxyglucose (18F-FDG)- positron emission tomography (PET)/computed tomography (CT) parameters in PC patients is controversial and no consensus exists as to its predictive capability. This meta-analysis was performed to comprehensively explore the prognostic significance of 18F-FDG-PET/CT parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 49 publications
2
19
1
1
Order By: Relevance
“…Glucose analog 18 F-fluorodeoxyglucose as metabolic tracer enables to recognize active metabolic areas such as in tumors or in infections. [ 17 ]…”
Section: Current Technical Innovationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose analog 18 F-fluorodeoxyglucose as metabolic tracer enables to recognize active metabolic areas such as in tumors or in infections. [ 17 ]…”
Section: Current Technical Innovationsmentioning
confidence: 99%
“…PET/CT is extensively used in diagnosing, staging, and post-therapy follow-up of PDAC. [ 16 17 ] A recent meta-analysis performed by Zhu et al . emerges the role of PET/CT as a prognostic factor to predict overall survival and event-free survival in PDAC.…”
Section: Current Technical Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it was shown that MTV (metabolic tumor volume) and TLG (total lesion glycolysis) values, measurable by FDG PET/CT, could be better than SUVmax alone for assessing and predicting entire tumor burden, overall metabolic activity and prognosis of several malignancies. [8][9][10] Recently, the correction of metabolic disorders and external replacement of decreased essential vitamins and minerals in patients before receiving chemotherapy and radiotherapy is considered as an adjunct to cancer treatment and thus, therapeutic response can be improved, the adverse effects of chemotherapy and radiotherapy can be better tolerated, and as a result patient's quality-of-life be improved. 3,4,11,12 However, measurement and evaluation of most of the specific vitamins and minerals are non-cost-effective and cause intensive labor and time loss.…”
Section: Introductionmentioning
confidence: 99%
“…Para medir esta captación, se han utilizado índices semicuantitativos que traducen la intensidad de captación de FDG en el tumor primario (valor de captación estándar: SUV), la masa tumoral activa (volumen tumoral metabólico: VTM), o una combinación de ambos (masa tumoral glicolítica: MTG) 8,12,13,14 . En un reciente metaanálisis sobre la utilidad pronóstica del PET/CT en cáncer pancreático, Zhu et al 15 recopilan la experiencia de 16 estudios en un total de 1.146 pacientes, y a pesar de la heterogeneidad de los resultados encontrados, concluyen que el valor de captación estándar máximo (SUVmax), VTM y MTG pudieran ser factores pronósticos significativos en estos pacientes. En nuestra revisión bibliográfica, no encontramos publicaciones referentes a la experiencia local ni regional en la evaluación de la utilidad pronóstica del PET/CT en cáncer pancreático.…”
unclassified